2011
DOI: 10.1002/lpor.201000019
|View full text |Cite
|
Sign up to set email alerts
|

3D THz metamaterials from micro/nanomanufacturing

Abstract: Metamaterials are engineered composite materials offering unprecedented control of wave propagation. Despite their complexity, effective properties can frequently be extracted by conceptualizing them as homogeneous and isotropic media with dispersive electric permittivity and magnetic permeability. For an ideal isotropic medium, strong dispersion in these properties causes wave and field vectors to form a left-handed (E,H,k)-frame involving backward waves, and offering control of quantities like the refractive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 214 publications
0
47
0
Order By: Relevance
“…Traditional planar metamaterials based on SRRs and their hybrid modifications have been extensively studied in recent years for demonstrating negative refraction, magnetoinductive waves, THz modulators and biological/chemical sensors [21][22][23][24][25][26][27][28].…”
Section: And References Therein)mentioning
confidence: 99%
“…Traditional planar metamaterials based on SRRs and their hybrid modifications have been extensively studied in recent years for demonstrating negative refraction, magnetoinductive waves, THz modulators and biological/chemical sensors [21][22][23][24][25][26][27][28].…”
Section: And References Therein)mentioning
confidence: 99%
“…Although the described advantages, the artificial metamaterials inevitably suffer from narrow operating bandwidths due to resonances, extremely limiting their practical applications. [19][20][21][22][23][24][25][26][27] Latest developments show that periodicity is not obligatory for metamateirals if the resonance response of unit cells predominantly manipulate the propagation of electromagnetic wave, 28 indicating superiority in comparison to photonic and phonon crystals. Our group's previous work showed that the strong coupling effects among the periodic unit cells can be effectively weakened by introducing defects into LHMs to eliminate periodicity.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, due to fabrication limitation [35,36] , most plasmonic metamaterials exhibiting PIT have been demon strated in planar or multi-layered structures by electric coup ling rather than by magnetic coupling [28, 30, 37 -40] . Recently, a number of plasmonic structures with magnetic resonances have also been proposed because of their potential advantages [41,42] .…”
Section: Introductionmentioning
confidence: 99%